How do you simplify #(5sqrt(2x)+sqrt5)(-4sqrt(2x)+sqrt(5x))#?

1 Answer
Sep 4, 2016

Answer:

#(5 sqrt(10) - 40) x + (5 - 4 sqrt (10)) sqrt(x)#

Explanation:

We have: #(5sqrt(2x)+sqrt(5))(-4sqrt(2x)+sqrt(5x))#

#=(5sqrt(2x)+sqrt(5))(sqrt(5x)-4sqrt(2x))#

Let's expand the parentheses:

#=(5sqrt(2x))(sqrt(5x))+(5sqrt(2x))(-4sqrt(2x))+(sqrt(5))(sqrt(5x))+(sqrt(5))(-4sqrt(2x))#

#=5sqrt(10x^(2))-20sqrt(4x^(2))+sqrt(25x)-4sqrt(10x)#

#=(5 cdot sqrt(10) cdot sqrt(x^(2)))-(20 cdot sqrt(4) cdot sqrt(x^(2)))+(sqrt(25) cdot sqrt(x))-(4 cdot sqrt(10) cdot sqrt(x))#

#=5 sqrt(10) x - 40x + 5 sqrt(x) - 4 sqrt(10) sqrt(x)#

#=(5 sqrt(10) - 40) x + (5 - 4 sqrt (10)) sqrt(x)#